Social Empowerment for Living Qur'an in Elderly Community Mukti Mulia - Syarif Hidayat (MUJAHADA: Jurnal Pengabdian Masyarakat, 2023)
This paper will reveal how social strengthening efforts are being made so that the Qur'an lives on in the elderly community, especially the mukti noble elderly community? This paper aims to reveal social strengthening efforts in reviving the Koran in the elderly community, especially the Mukti Mulia elderly community. The method used in this social strengthening effort uses a participatory approach to the elderly community, education and training for the community, building networks and partnerships, advocacy related to various community policies and community empowerment to support social reinforcement in enlivening the Qur'an in the elderly community Mukti Mulia.